VD_FINDINFO HC / 2012 / 682 vom 29. Oktober 2012 - VD Tribunal cantonal (2012)
COMPÉTENCE RATIONE MATERIAE, DÉCISION D'IRRECEVABILITÉ | 134 al. 3 CC, 308 CPC (CH), 59 al. 2 let. b CPC (CH), 60 CPC (CH)